A novel surgical intervention using transvaginal endoscopic ultrasonography for the children with OHVIRA syndrome - Michiaki Ikegami; Toshiaki Takahashi; Satoshi Shiojima; Yashiro Yoshizawa; Masaharu Kimata; Hiroko Konno; Yumi Shimizu; Mao Ikari; Yurina Taira (Elsevier, 2023)
Background: Obstructed Hemivagina and Ipsilateral Renal Anomaly (OHVIRA) syndrome is characterized by duplicated uterus and vagina, obstructed hemivagina, and ipsilateral congenital renal malformation. Patients typically have progressive hematocolpos and hematometra when they first show up after menarche. Hematocolpos symptoms can be effectively treated with a vaginal septectomy and hematoma drainage. However, current described procedures to perform the vaginoscopic incision of the vaginal septum carry intraoperative complications in pediatric patients. We aim to discuss our novel operative procedure of vaginal septectomy using transvaginal endoscopic ultrasonography (EUS) for the children with OHVIRA syndrome. Case presentation: A 12-year-old girl was referred to our hospital because of excruciating abdominal pain after her menarche. Magnetic resonance imaging showed hematocolpos and hematometra, and OHVIRA syndrome was diagnosed. Elective vaginal septectomy was planned. With the use of a resectoscope and transvaginal EUS, we carried out transvaginal septectomy. The procedure was completed safely, and there were no postoperative problems. Conclusions: We discovered that EUS-guided transvaginal septectomy is a safe, technically feasible, and minimally invasive approach with low incidence of intraoperative complications for treating OHVIRA syndrome in children with hematocolpos.